NDALEM PADMASUSASTRO SEBAGAI RUANG PERTUNJUKAN ALAM NATURAL (Ndalem Padmasusastro as a natural performing stage) - Efrida Efrida (Institut Seni Indonesia Surakarta, 2000)
Space (is) esensial element in a(n show. Space become the place of to artistic expression blaze outburst explosion of feeling. Natural spaceÂ (of)Â natural with strong column value and character have potency to become a show space. This matter (is) determined by sensitivity (of) choreographer to catch strength (of] potency and space a space so that can mengekplorasinya maximally to ajang afn show. Ndalem Padmasusastro with joglo house building and wide [of] background representing air-gap which consist of some space where each space have different space value and characterIts existence as natural show space [of) natural at the same time as public space make Nda!em Padmasusastro as space capable to accommodate incoming public importance and give freedom (at] public to determine (by] xself focus their attention and express artistic (soul! head] (of) them to show which look on is theÂ Keyword: Ndalem Padmasusastra, natural show space (of) natural, space.